2015
DOI: 10.5539/ijef.v7n4p99
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness and Unemployment in the Eurozone

Abstract: The paper analyzes the long term dynamics of the relationship between the competitiveness and the unemployment in the Eurozone, with the emphasis on the "North" and "South" differences. Using the productivity per person as a proxy for competitiveness, it shows both the differences between the North and South of the Eurozone and the differences between the pre-crisis and crisis periods in both areas. Moreover, it demonstrates that the relationship between the competitiveness and unemployment is negative in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Our findings are in line with those of Chen et al (2007), Gallegati et al (2014), Rusek (2015), Chen (2017) andWorld Bank Group (2017).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Our findings are in line with those of Chen et al (2007), Gallegati et al (2014), Rusek (2015), Chen (2017) andWorld Bank Group (2017).…”
Section: Resultssupporting
confidence: 94%
“…Significant direct relationship between innovation of entrepreneurial activities and competitiveness Cantwell 2003;Özçelik and Taymaz 2004;Ghoniem and El Khouly 2012;Petrariu et al 2013;Huggins et al 2014;Ciocanel and Pavelescu 2015;Dogan 2016;Matos Ferreira et al 2017;Herman 2018 Positive correlation between employment and increase in competitiveness Moser et al 2010;Martus 2013;Rusek 2015;OECD 2016;World Bank Group 2017 Negative relationship between high job creation expectation rate and economic competitiveness Chen et al 2007;Gallegati et al 2014 Entrepreneurial activity and competitiveness have been the research topic of a large number of authors, enjoying increased attention on how entrepreneurs innovate and consequently contribute to higher levels of competitiveness. Reviewing the literature, we can assert that the quality of entrepreneurship, measured by innovation and job creation, is important in order to achieve economic competitiveness.…”
Section: Findings Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…No studies were found that relate these two variables. However, some authors indicate that there is a negative relationship between high job creation expectations and economic competitiveness [72,73].…”
Section: Discussion Of the Results Of The Linear Regression Equation mentioning
confidence: 99%